2020
DOI: 10.1371/journal.pgen.1009100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of both exonic and intronic variants for effects on RNA splicing allows for accurate assessment of the effectiveness of precision therapies

Abstract: Elucidating the functional consequence of molecular defects underlying genetic diseases enables appropriate design of therapeutic options. Treatment of cystic fibrosis (CF) is an exemplar of this paradigm as the development of CFTR modulator therapies has allowed for targeted and effective treatment of individuals harboring specific genetic variants. However, the mechanism of these drugs limits effectiveness to particular classes of variants that allow production of CFTR protein. Thus, assessment of the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 82 publications
2
19
1
Order By: Relevance
“…These results were similar with those of the present study, showing 94.5% sensitivity and 94.3% specificity with a cut-off value of >0.22. The present study might be highlighted in that a large number of variants of NF1 were evaluated, since previous studies using SpliceAI evaluated mainly variants of BRCA1/BRCA2 , CFTR , FBN1 , and PLCγ1 genes [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar with those of the present study, showing 94.5% sensitivity and 94.3% specificity with a cut-off value of >0.22. The present study might be highlighted in that a large number of variants of NF1 were evaluated, since previous studies using SpliceAI evaluated mainly variants of BRCA1/BRCA2 , CFTR , FBN1 , and PLCγ1 genes [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, many +2T>C variants in human disease genes that have been capable of generating some wild-type transcripts are likely to have gone largely unreported; this represents a significant deficiency in terms of our understanding of genotype-phenotype relationships and tailored treatment options given that even the minor retention of wild-type transcripts derived from a variant allele might significantly impact disease expression and severity (Ramalho et al, 2002;Den Uijl et al, 2011;Raraigh et al, 2018;Lin et al, 2019;Scalet et al, 2019;Joynt et al, 2020). In this regard, it is pertinent to mention that CFTR c.3873+2T>C and c.4242+2T>C transitions (Joynt et al, 2020) and SRP68 c.184+2T>C (Schmaltz-Panneau et al, 2021) are among the most recently reported examples of disease-causing +2T>C variants that generated some wild-type transcripts. Secondly, +2T>C variants in human disease genes may not invariably be pathogenic, a notion that has received support from at least two recent publications, which reclassified BRCA2 c.8331+2T>C (Nix et al, 2021) and BAP1 c.783+2T>C (Goldberg et al, 2021) as variants of unknown significance.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 21, 2021. ; https://doi.org/10.1101/2021.05.20.21257549 doi: medRxiv preprint research could evaluate its pathogenic potential in Peruvian populations (Joynt et al, 2020, Lin et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…However, intronic variants are known to have functional impacts on RNA splicing patterns (Cooper, 2010). To elucidate the functional significance of this variant, future research could evaluate its pathogenic potential in Peruvian populations (Joynt et al, 2020, Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%